(untitled) (Proceedings of International Conference on Special Education, 2017)
While students with MDVI are at school, they receive various supports from their school system. Educators and related service providers explore teaching strategies and activities with the students in an effort to ensure their success in life. However, through our experience, those supports are not enough to prepare students with adequate skills and services needed when they become adults. In Indonesia, many schools for students with MDVI have residential programs. This environment can restrict their chance of learning in a natural environment. Students do not have the opportunity to interact with other people other than their teachers and family. They also become secluded from their community, causing the community to develop a negative stigma about students with disabilities. In Bhakti Luhur Bandung, a partnership was created between the school and villagers in a local farming community. Students work with villagers on the farm, where the students learn to identify, plant and cook vegetables from the garden. The farming partnerhsip, which started in 2014, provides an essential functional learning opportunity for the students. The farm involves 10 Villagers who happily teach the students, although they don’t have any background working with students with MDVI. Currently, students sell their crops in the local market, which allows them to become more visible and recognized in the community.This presentation will share testimony from the villagers, values and beliefs about students with MDVI, and the impact of strengthening the relationships within communities. This relationship expanded the worlds of both the children and the community.